Firearms Injury Prevention Program - McManus, Alexandra (University of Otago, 2000)
The Firearm Arm Injury Prevention Project was conducted to evaluate the effectiveness of an intervention to reduce the access to means of suicide in a rural community in western Australia with a suicide rate in young men three times that of the States. The multifacted project had the full support of the community and was extremely successful.